Pelatihan Pendidikan Politik Untuk Meningkatkan Kapasitas Kepemimpinan Kader Partai Politik Perempuan di Provinsi DKI Jakarta - Nurdin Nurdin; Fatkhuri Fatkhuri (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
The level of political representation of female political party cadres in regional legislatures has not yet reached a minimum of 30%. This condition is caused by various internal and external factors that hinder the progress of female cadres to compete with male cadres. One of the obstacles and challenges faced by these female cadres is the weak leadership capacity. Female cadres cannot compete with male cadres in the contestation for the provincial legislative elections. The cadres must be able to increase their leadership capacity if they want to be able to compete with male cadres. The purpose of this training is to increase the leadership capacity of female political party cadres as a strategy to win seats in the DKI Jakarta Provincial House of Representatives. The methods used are education, training and simulation. The results achieved show that the training participants have gained understanding and skills in formulating strategies for winning the legislative elections for the next period.